Analysis of Tax Literacy, Digital Literacy, and the Implementation of the CoreTax Application on Individual Taxpayer Compliance at KPP Madya Surabaya - Siprianus Dargo; Aprilianus Adiputra; Aloisius Hama (Citakonsultindo, 2026)
This study aims to empirically analyze how tax literacy affects individual taxpayer compliance and to examine the role of digital literacy as a moderating factor that strengthens the relationship between tax literacy and tax compliance. In addition, this research explores the impact of using the Coretax application on taxpayer compliance, as well as the simultaneous relationship among tax literacy, digital literacy, and Coretax application usage on compliance levels. The study employs a quantitative descriptive approach with multiple linear regression analysis to test the influence of independent variables on the dependent variable. The research population comprises individual taxpayers registered at KPP Madya Surabaya, totaling 3,507 individuals, with a sample of 50 respondents. The results indicate that tax literacy, digital literacy, and the Coretax Application Usage significantly affect taxpayer compliance levels. Overall, these three variables contribute substantially to enhancing taxpayer compliance. These findings provide empirical evidence of the importance of tax literacy, digital literacy, and the utilization of technological applications in supporting tax compliance among individual taxpayers.